TNFSF13B rs9514828 gene polymorphism and soluble B cell activating factor levels: Association with apical periodontitis - Cruz, Alvaro; Gascón, Luis Gerardo; Palafox-Sánchez, Claudia Azucena; Flores-García, Christian; Espinoza-García, Noemí; Sagrero-Fabela, Nefertari; Cintra, Luciano Tavares Angelo [UNESP]; Mejía-Flores, Rocío; Salazar-Camarena, Diana Celeste (Wiley, 2023)
Aim: The aim of this case-control study was to evaluate the association between the TNFSF13B rs9514828 (−871 C > T) polymorphism and soluble BAFF (sBAFF) in apical periodontitis (AP) patients. Methodology: Two hundred and sixty one healthy subjects (HS) and 158 patients with AP classified as: 46 acute apical abscess (AAA), 81 primary AP (pAP) and 31 secondary AP (sAP) patients were included. Genomic DNA (gDNA) was extracted from peripheral blood cells according to the salting out method. The TNFSF13B rs9514828 (NC_000013.11:g.108269025C > T) were identified using polymerase chain reaction (PCR) followed by restriction fragment length polymorphisms (RFLP). Serum sBAFF levels were measured by ELISA test. The chi-squared or Fisher's exact test was performed. Odds ratios (OR) and 95% confidence intervals (95% CI) were calculated to evaluate the risk of AP associated with the rs9514828. The Mann–Whitney U test and Kruskal–Wallis analysis were used for non-normally distributed data. Differences were considered significant with a p-value <.05. Results: No differences in the genotype/allele frequencies were shown between HS and patients with AAA. However, the TT genotype (OR = 2.68, 95% CI: 1.10–6.53; p =.025) and T allele (OR = 1.46, 95% CI: 1.00–2.12; p =.045) were associated with increased risk of pAP. In contrast, the minor allele T significantly decreased the risk of sAP (OR = 0.49, 95% CI: 0.024–0.99; p =.043). sBAFF serum levels were increased in AAA and pAP compared with HS (p <.01 and p =.021, respectively). The AAA patients had higher sBAFF serum levels than pAP (p =.034) and sAP (p <.01). Conclusions: These results suggest that the TNFSF13B rs9514828 (−871 C > T) polymorphism is associated with pAP susceptibility and that BAFF is a cytokine that might be involved in acute and chronic AP. The future exploration of the rs9514828 polymorphism in other AP cohorts is recommended.
Keywords: acute apical abscess; apical periodontitis; rs9514828; sBAFF; TNFSF13B polymorphisms